Ectopic ULBP2 Is Associated with Decreased NKG2D Expression in CD8+ T Cells Under T Cell-Modulatory Conditions in a Murine Tumor Model - Yasuhiko Teruya; Kosuke Yamaguchi; Kohei Yamane; Naomi Miyake; Yuji Nakayama; Takafumi Nonaka; Hiroki Chikumi; Akira Yamasaki (Cells)
UL16-binding protein 2 (ULBP2), a ligand for the activating receptor NKG2D, plays a dual role in tumor immunity, promoting immune activation or suppression, depending on the context. To investigate its impact on CD4+CD25+ T cell-targeted immunotherapies, we used a syngeneic CT26 colon cancer model engineered to express ULBP2 and compared tumor growth and tumor-infiltrating lymphocyte (TIL) profiles in control and ULBP2-expressing tumors treated with anti-CD4, anti-CD25, or anti-CTLA-4 antibodies. Tumor growth was uniformly assessed on day 21 post-transplantation, and TIL analysis was performed in groups with evaluable residual tumors. Anti-CD4 antibody significantly suppressed tumor growth in mock-transfected tumors, while no significant suppression was observed in ULBP2-expressing tumors. Anti-CD25 antibody had limited efficacy in mock tumors and tended to promote tumor growth in ULBP2-expressing tumors. Following these treatments, ULBP2 expression was associated with reduced NKG2D expression in CD8+ effector memory T cells, particularly PD-1high subsets. In contrast, anti-CTLA-4 antibody treatment induced marked tumor regression irrespective of ULBP2 expression. These findings suggest that ULBP2–NKG2D signaling may contribute to altered CD8+ T cell phenotypes under T cell-modulatory conditions, potentially impacting the outcome of CD4+CD25+ T cell-targeted therapies and providing insights for optimizing immunotherapeutic strategies.